Corpus Callosum Agenesis Presented With Attention Deficit Hyperactivity Disorder: Two Case Reports - Musa Sahpolat; gonca celik; ayse avci; aysegul tahiroglu (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
ADHD is a treatable neuropsychiatric disorder which can continue till adulthood. There have been three subtypes including attention deficiency, hyperactivity and impulsivity. Its etiology remains unclear yet. It is hypothesized that there is an impairment of neurodevelopment in early developmental periods through the interactions between genetic and environmental processes. Corpus callosum provides an integration of cognitive, sensorial and motor functions of brain as a response to the impulses originating from the cortex. The damage of this region may result in deterioration of some cerebral functions such as cognitive functions, speaking, learning ability and impulse control. In this paper, we report two pediatric cases who had comorbid attention deficiency and corpus callosum agenesis without mental retardation. [Cukurova Med J 2013; 38(4.000): 759-764]